(untitled) (Research, Society and Development, 2023)
Fetal death is the death of a product of conception before expulsion or complete extraction from the mother’s body, regardless of the duration of pregnancy. Perinatal death encompasses the death of a fetus from a gestational age of 22 weeks to 7 days postnatally. Such information is extremely relevant for studies in public health and maternal and child health, and understanding the main causes of fetal and perinatal death is essential for its prevention. Given the above, the present study aimed to quantify and relate the epidemiological information of the municipality of Cascavel and the rates of fetal and perinatal deaths that occurred This is a retrospective study with the analysis of death certificates registered at the Epidemiological Surveillance Center of the municipality of Cascavel, PR, between January 1, 2014 and December 31, 2018. The predominant underlying cause in fetal deaths was “fetus affected by maternal conditions” and the predominant underlying cause of perinatal deaths was “fetus or newborn affected by maternal complications in pregnancy”. The year with the highest number of fetal deaths was 2017 and the year with the highest number of perinatal deaths was 2014.